2017
DOI: 10.1038/modpathol.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic intraductal tubulopapillary neoplasm is genetically distinct from intraductal papillary mucinous neoplasm and ductal adenocarcinoma

Abstract: Intraductal tubulopapillary neoplasm is a relatively recently described member of the pancreatic intraductal neoplasm family. The more common member of this family, intraductal papillary mucinous neoplasm, often carries genetic alterations typical of pancreatic infiltrating ductal adenocarcinoma (KRAS, TP53, and CDKN2A) but additionally has mutations in GNAS and RNF43 genes. However, the genetic characteristics of intraductal tubulopapillary neoplasm have not been well characterized. Twenty-two intraductal tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 91 publications
7
53
3
Order By: Relevance
“…The three lesions in this study were genetically consistent with these characteristics, whereas none of the lesions harbored any KRAS/GNAS/BRAF mutations. Some studies have shown that ITPN can also be linked to PIK3CA mutations [ 24 26 ], but this was not observed in the present case. However, PIK3CA mutations occur in less than 30% of cases; thus, ITPN is still highly probable despite its absence in our samples.…”
Section: Case Presentationcontrasting
confidence: 81%
See 1 more Smart Citation
“…The three lesions in this study were genetically consistent with these characteristics, whereas none of the lesions harbored any KRAS/GNAS/BRAF mutations. Some studies have shown that ITPN can also be linked to PIK3CA mutations [ 24 26 ], but this was not observed in the present case. However, PIK3CA mutations occur in less than 30% of cases; thus, ITPN is still highly probable despite its absence in our samples.…”
Section: Case Presentationcontrasting
confidence: 81%
“…About 40 to 60% of IPMNs reportedly harbor GNAS mutations alone, and the vast majority of IPMNs harbor KRAS and/or GNAS mutations [ 21 23 ]. Conversely, ITPN lacks KRAS/GNAS/BRAF mutations [ 2 , 24 26 ]. The three lesions in this study were genetically consistent with these characteristics, whereas none of the lesions harbored any KRAS/GNAS/BRAF mutations.…”
Section: Case Presentationmentioning
confidence: 99%
“…Thus, the initial studies based on the analysis of only very limited number of IPTN tumors showed, at variance with IPMN tumors, a low frequency of KRAS (0–10%), GNAS (0–25%), TP53 (= −23%), SMAD4 (0–10%) and RNF43 (0–10%) mutations; more frequent were the CDKN2A alterations (54%) reviewed in [ 70 ]. In a recent study, Basturk and coworkers reported the analysis of the molecular abnormalities occurring in 22 IPTN tumors, showing that: most of the previously-reported IPMN genetic abnormalities were absent; loss of CDKN2A was observed in 25% of cases; MAPK genes were not frequently altered; chromatin remodeling genes (such as MLL1 , MLL2 , MLL3 , BAP1 ) were altered in 32% of cases; PI3K pathway genes were altered in 27% of cases; finally, 18% of tumors displayed FGFR2 fusions [ 71 ]. According to these data, it was concluded that IPTN is a distinct clinicopathologic entity and is genetically distinct from IPMN and PDAC [ 71 ].…”
Section: Genetic Abnormalities Of Pancreatic Intraductal Tubulopapmentioning
confidence: 99%
“…Research has established that somatic FGFR2 alterations play a crucial role in the origin of numerous solid tumours and that alterations in the activity (overexpression) are associated with a poor outcome in certain cancer types. Interestingly, many of these malignancies display a papillary structure and/or an adenocarcinoma morphology like ADPA, pointing to common underlying molecular mechanisms . Oncogenic activation of FGFR2 is supposed to have a key role in the dysregulation of cell division (proliferation), cell movement and in the development of new blood vessels that nourish a growing tumour .…”
Section: Discussionmentioning
confidence: 99%